Acclimation to hypoxia in Chlamydomonas reinhardtii: can biophotolysis be the major trigger for long‐term H2 production?. Issue 4 (8th August 2014) - Scoma, Alberto; Durante, Lorenzo; Bertin, Lorenzo; Fava, Fabio
Summary In anaerobiosis, the microalga Chlamydomonas reinhardtii is able to produce H2 gas. Electrons mainly derive from mobilization of internal reserves or from water through biophotolysis. However, the exact mechanisms triggering this process are still unclear. Our hypothesis was that, once a proper redox state has been achieved, H2 production is eventually observed. To avoid nutrient depletion, which would result in enhanced fermentative pathways, we aimed to induce long‐lasting H2 production solely through a photosynthesis : respiration equilibrium. Thus, growing cells were incubated in Tris Acetate Phosphate (TAP) medium under low light and high chlorophyll content. After a 250‐h acclimation phase, a 350‐h H2 production phase was observed. The light‐to‐H2 conversion efficiency was comparable to that given in some reports operating under sulphur starvation. Electron sources were found to be water, through biophotolysis, and proteins, particularly through photofermentation. Nonetheless, a substantial contribution from acetate could not be ruled out. In addition, photosystem II (PSII) inhibition by 3‐(3, 4‐dichlorophenyl)‐1, 1‐dimethylurea (DCMU) showed that it actively contributed to maintaining a redox balance during cell acclimation. In appropriate conditions, PSII may represent the major source of reducing power to feed the H2 evolution process, by inducing and maintaining an ideal excess of reducing power.